EFEKTIVITAS KOMITE AUDIT, KUALITAS AUDIT DAN MANAJEMEN LABA (Studi Empiris Perusahaan yang Terdaftar di Indeks LQ45 pada Tahun 2014-2018) - Fefi Arni Sirait; Abdul Rohman (Diponegoro Journal of Accounting, 2020)
Every company certainly has hope to obtain high and stable earnings because earnings are used as the main indicator to measure company performance, so as many companies do earnings management practices if the expected profit targets unfulilled. The purpose of this study is to examine the effect of audit committee effectiveness and audit quality with proxy KAP Big4, audit fee and audit tenure on earnings management. On the basis of the theory of agency, that is regarding the agent's relationship with the principal, then it should be the higher the effectiveness of the audit committee and audit quality, the higher its influence in minimizing earnings management.The population in this study are companies listed in the LQ45 index in 2014-2018 with a sample of 153 companies listed in the LQ45 index in 2014-2018. The analytical tool used is multiple regression analysis.The results of this study indicate that the auditors of KAP Big4 and audit fee have a negative and significant effect on earnings management, the effectiveness of the audit committee has a negative and not significant effect on earnings management while the audit tenure has no effect on earnings management. With this result it can be said that if a company uses KAP Big4 and the higher the audit fee then the lower the level of earnings management practices, the effectiveness of the audit committee has a negative and not significant effect and does not affect audit tenure it might be influenced by several other factors.